ANALISIS INTERNAL DAN EKSTERNAL PENGELOLAAN PERIKANAN PANTAI SKALA KECIL DI KOTA TEGAL (An Internal and External Analysis of Small-Scale Coastal Fisheries Management in Tegal City) - Agnes P. Sudarmo; MS. Baskoro; Budy Wiryawan; Eko S. Wiyono; Daniel R. Monintja (Bogor Agricultural University, 2016)
ABSTRACTThe problems that occur in coastal areas related to the management of small-scale coastal fisheries in Tegal are the depletion of fish resources in coastal waters, and a variety of pressures including pressure due to population growth, abrasion as well as water pollution. A holistic understanding of internal and external factors of coastal fisheries management is needed to determine how these factors affect the fishing activities in Tegal. The purpose of this research is to analyze the internal and external factors of small-scale coastal fisheries management in Tegal. The benefit of this research is to give feedback to stakeholders and constructive actions in creating sustainable management of coastal fisheries. This study was conducted in Tegal precisely in the village of Muarareja. The sample in this study is 64 small-scale fishermen, using purposive sampling. Primary data were collected by using questionnaires, secondary data were obtained from Departementnof Agriculture and Marine Tegal, Bureau of Statistics of Tegal, Muarareja Fish Auction. Data were analyzed using descriptive analysis and SWOT analysis. The results showed that the present status of coastal fisheries management in Tegal is currently categorized as